2017
DOI: 10.1007/s11682-017-9723-x
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of risky decision making in adolescents reporting frequent alcohol and/or marijuana use

Abstract: Because adolescence is a period of heightened exploration of new behaviors, there is a natural increase in risk taking including initial use of alcohol and marijuana. In order to better understand potential differences in neurocognitive functioning among adolescents who use drugs, the current study aimed to identify the neural substrates of risky decision making that differ among adolescents who are primary users of alcohol or marijuana, primary users of both alcohol and marijuana, and controls who report prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 68 publications
2
26
0
Order By: Relevance
“…However, the current findings are consistent with some extant literature indicating that internalizing psychopathology, including depression and anxiety, is associated with decreased intra-SN connectivity (Liao et al, 2011 ; Manoliu et al, 2014 ). Notably, research on risk-taking has found that increased functional connectivity between the dACC and right anterior insula is associated with risky decision-making and externalizing behavior (e.g., alcohol/nicotine use; Claus et al, 2011 , 2017 ; Wei et al, 2016 ). In light of the current findings, connectivity within this anterior insula-dACC circuit appears to index motivational/reward-seeking behavior, and thus the negative association between connectivity and harm avoidance may reflect a maladaptive propensity for risk aversion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current findings are consistent with some extant literature indicating that internalizing psychopathology, including depression and anxiety, is associated with decreased intra-SN connectivity (Liao et al, 2011 ; Manoliu et al, 2014 ). Notably, research on risk-taking has found that increased functional connectivity between the dACC and right anterior insula is associated with risky decision-making and externalizing behavior (e.g., alcohol/nicotine use; Claus et al, 2011 , 2017 ; Wei et al, 2016 ). In light of the current findings, connectivity within this anterior insula-dACC circuit appears to index motivational/reward-seeking behavior, and thus the negative association between connectivity and harm avoidance may reflect a maladaptive propensity for risk aversion.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitudes of differences in problems remained when comparing drunk driving among people who simultaneously use alcohol and cannabis to people who only use concurrently (Subbaraman & Kerr, 2015). People who are under the combined influence of alcohol and cannabis may be more likely to make decisions leading to intoxicated driving than people who are only under the influence of either alcohol or cannabis (Claus et al, 2018). Importantly, among individuals who used both cannabis and alcohol, simultaneous use was almost twice as prevalent as concurrent use, suggesting that this may be an important issue for further study.…”
Section: Introductionmentioning
confidence: 99%
“…Functional MRI studies in co-users have shown dysfunction in frontal and temporal regions, and a decoupled association between hippocampal symmetry and verbal learning (Schweinsburg et al, 2005 , 2011 ; Medina et al, 2007b ). An fMRI study found decreased BOLD response in the thalamus, insula, and striatum versus non-users when taking risks (Claus et al, 2018 ). A cross-sectional DTI study by Bava et al ( 2009 ) showed altered frontoparietal networks and fiber projections within circuits responsible for the modulation of complex sensory, motor, and cognitive processing, namely in fibers of the postcentral gyrus, splenium of the corpus callosum, inferior frontal region, and left superior longitudinal fasciculus.…”
Section: Co-usementioning
confidence: 99%